Gazeta do Norte newspaper and the great Sports Square as nation projects: 'Mold for Tomorrow's Men!' - Rogério Othon Teixeira Alves; Luciano Pereira da Silva; Ester Liberato Pereira; Georgino Jorge de Souza Neto; Fernanda de Souza Cardoso; Carlos Rogério Ladislau (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study contextualizes the establishment of Montes Claros Sports Square, in Minas Gerais, through the look of Gazeta do Norte newspaper, and its alignment with a nation project to be established by the government of Getúlio Vargas, who took office in 1930. He formulated actions for a 'national reconstruction' project, for which, from society, it was necessary to emerge both physically and morally healthy subjects, fundamental conditions for the construction of the aforementioned new nation, and which could reach the Brazilians in the hinterlands. Thus, this study aimed to narrate a history of the construction of Montes Claros Sports Square, from the end of the 1930s until 1945, during Getúlio Vargas' first term as President of the Republic, with Benedito Valadares as Governor of Minas Gerais. Methods: The study was based on the extensive collection of data researched in Gazeta do Norte newspaper. Results: Symbol of a modern project for sports, the Sports Square was announced by the governor during his visit to the city, in January 1939, and established on the Oswaldo Cruz meadow. It is possible to verify that, notably, in the 15 years of Getúlio Vargas' first term, the practice of sports is developed and consolidates itself as an 'actor' in the social space of Montes Claros. Conclusion: In this city, in addition to the construction of the Sports Square, it was necessary to educate and inform the individuals. It can be said that the newspaper Gazeta do Norte firmly contributed to Vargas' nation project.